2021
DOI: 10.1038/s41467-021-27124-8
|View full text |Cite
|
Sign up to set email alerts
|

The NUCKS1-SKP2-p21/p27 axis controls S phase entry

Abstract: Efficient entry into S phase of the cell cycle is necessary for embryonic development and tissue homoeostasis. However, unscheduled S phase entry triggers DNA damage and promotes oncogenesis, underlining the requirement for strict control. Here, we identify the NUCKS1-SKP2-p21/p27 axis as a checkpoint pathway for the G1/S transition. In response to mitogenic stimulation, NUCKS1, a transcription factor, is recruited to chromatin to activate expression of SKP2, the F-box component of the SCFSKP2 ubiquitin ligase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 80 publications
(109 reference statements)
0
26
0
Order By: Relevance
“…Nuclear casein kinase and cyclin-dependent kinase substrate 1 (NUCKS1), involved in homologous recombination, is lost from chromatin upon etoposide treatment and at 24 hours release. This transcription factor binds chromatin in a cell cycle-dependent manner and its levels increase in late G1, thus explaining this enrichment on chromatin (Hume et al , 2021; Parplys et al , 2015). Similarly, structural maintenance of chromosome 4 (SMC4), a component of the condensin complex facilitating the sister-chromatid condensation and mitosis, which is also involved in DNA repair (Wang & Wu, 2021), is depleted from chromatin immediately after etoposide treatment, but unlike NUCKS1, it is fully restored to basal levels 24 hours after release.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear casein kinase and cyclin-dependent kinase substrate 1 (NUCKS1), involved in homologous recombination, is lost from chromatin upon etoposide treatment and at 24 hours release. This transcription factor binds chromatin in a cell cycle-dependent manner and its levels increase in late G1, thus explaining this enrichment on chromatin (Hume et al , 2021; Parplys et al , 2015). Similarly, structural maintenance of chromosome 4 (SMC4), a component of the condensin complex facilitating the sister-chromatid condensation and mitosis, which is also involved in DNA repair (Wang & Wu, 2021), is depleted from chromatin immediately after etoposide treatment, but unlike NUCKS1, it is fully restored to basal levels 24 hours after release.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we presume that p27 is a downstream factor of p53 and plays a role in suppressing anchorage-independent growth of cancer cells, which might be involved in promoting metastasis upon p53 inactivation. Recently, Hume et al, 2021. have reported that DNA damage induces p53-dependent transcriptional repression of NUCKS1, a positive regulator for a p27-targeting module SKP2 of the ubiquitin ligase SCF SKP2 , leading to an increase in p27 protein (Hume et al, 2021). This p53-dependent regulatory pathway for suppressing p27 degradation might also be involved in the anchorage-independent growth.…”
Section: Discussionmentioning
confidence: 99%
“…6D). p53 is involved in regulating cycle-related proteins including P21 and P27 [26]. The nuclear accumulation of p53 could activate its functions [27].…”
Section: Xpo1 Inhibitor Kpt-330 Activated P53/mtor Pathway To Induce ...mentioning
confidence: 99%